2020
DOI: 10.18203/issn.2454-5929.ijohns20201686
|View full text |Cite
|
Sign up to set email alerts
|

Threshold shift validity by documenting sensorineural acuity level: a useful tool for masking

Abstract: <p class="abstract"><strong>Background:</strong> Masking dilemma is a condition prevalent whenever there is significant hearing loss in non-test ear and conductive hearing loss in test ear resulting into narrow or non-existent plateau width. Three feasible ways are divulged to circumvent this condition namely, Sensorineural acuity level testing, Fusion Inferred at threshold and use of insert type transducers. Different circumstances encountered when using insert type transducers and Fusion In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The SAL normative values obtained in the current study are in accordance with the previous findings reported by Awang et al [13] and Kapoor et al [23]. It is worth stating that both studies used the B81 bone vibrator to establish the SAL normative values among healthy Asian adults.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The SAL normative values obtained in the current study are in accordance with the previous findings reported by Awang et al [13] and Kapoor et al [23]. It is worth stating that both studies used the B81 bone vibrator to establish the SAL normative values among healthy Asian adults.…”
Section: Discussionsupporting
confidence: 91%
“…That is, it is problematic if the genuine BC thresholds are not established as the type of hearing loss could not be confirmed subsequently (leading to an incomplete hearing diagnosis). It is worth stating that overmasking is a common problem in the PTA testing and must be carefully addressed [12,13,23]. The SAL test is valuable in determining masked BC thresholds in cases of overmasking so that an accurate hearing diagnosis can be made.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the type of bone oscillator was not stated in the study by Jerger and Tillman [19]. On the other hand, in a study by Kapoor et al involving 50 normal-hearing Indian adults (n = 100 ears) aged 18 to 60 years old [33], the SAL normative data were measured using the Radioear B81 bone vibrator. The median SAL normative data were 40 dB at 250 Hz, 60 dB at 500 Hz, 60 dB at 1000 Hz, 55 dB at 2000 Hz, and 50 dB at 4000 Hz.…”
Section: Discussionmentioning
confidence: 98%